Basic Alumina‐Supported Synthesis of Aryl‐Heteroarylmethanes via Palladium Catalyzed Cross‐Coupling under Microwave Irradiation. (25th March 2013) - Sahu, Krishnendu B.; Maity, Arindam; Mondal, Shyamal; Paira, Rupankar; Saha, Pritam; Naskar, Subhendu; Hazra, Abhijit; Banerjee, Sukdeb; Mondal, Nirup B.
Abstract : A basic alumina‐supported microwave assisted simple methodology has been developed for the synthesis of aryl‐heteroaryl methanes (benzylated quinolones) via transition metal catalyzed cross‐coupling reaction of halo substituted polynuclear oxa‐aza quinolones with benzyl indium, an organometallic reagent easily derived from commercially available benzyl bromide. Abstract :